Perkembangan Pendidikan Jaman Yunani Dan Romawi Hingga Abad Pertengahan Di Eropa - Kusmawati, Heny; Nisa’, Nurun; Marzuki, Mahmud Alam; Aziz, Zilqi Wahyu Fatkhurrohman (Global Education Journal, 2023)
The author is interested in researching the development of education from ancient Greece and Rome to the Middle Ages in Europe. Education, as a form of human effort, aims to benefit individuals and remains an integral part of human life. Over time, science has rapidly evolved, with early recognition of Greece as the birthplace of Western culture. Greek civilization, influenced by both Eastern and Western cultures, contributed to the emergence of three distinct nations: Aegae-Creta, Aryans, and Dorians. During Roman times, education aimed to cultivate loyal and courageous citizens, prepared for sacrificial service to their homeland. However, with the rise of Hellenism and the influence of Greek philosophers, a cultural shift occurred, leading to an increased awareness among the Romans of the importance of knowledge. Consequently, the educational goal evolved to focus on shaping well-rounded individuals.